Mapping community-sensitive interventions for promoting mental health in high schools: a scoping review - Marcos Roberto Vieira Garcia; Vera Silvia Facciola Paiva (Revista Latinoamericana de Psicopatologia Fundamental)
This scoping review evaluated community-sensitive mental health promotion projects in high schools. In total, 15 papers were selected from six major bibliographic databases. Results showed that these programs conceptualize mental health as socially constructed projects, highlighting the need for interventions that are tailored to specific communities in school settings. Challenges included forming partnerships within school communities, responding to unforeseen demands, obtaining funding in contexts that favor universal approaches and prioritize individualized focus, and linking academic and community knowledge. Incorporating human rights-based approaches involves addressing social inequalities and human rights in school mental health interventions. Addressing the social determinants of mental health in school-based programs requires innovative theoretical and methodological intervention models.